Metabolic alteration of circulating steroid hormones in women with gestational diabetes mellitus and the related risk factors - Yang, Na; Zhang, Wei; Ji, Cheng; Ge, Jiajia; Zhang, Xiaoli; Li, Meijuan; Wang, Min; Zhang, Tianqi; He, Jun; Zhu, Huaijun (Frontiers in Endocrinology, 2023)
Background: Abnormally changed steroid hormones during pregnancy are closely related to the pathological process of gestational diabetes mellitus (GDM). Our aim was to systematically profile the metabolic alteration of circulating steroid hormones in GDM women and screen the risk factors. Methods: This study was a case-control study with data measured from 40 GDM women and 70 healthy pregnant women during their 24-28 gestational weeks. 36 kinds of steroid hormones, including 3 kinds of corticosteroids, 2 kinds of progestins, 5 kinds of androgens and 26 kinds of downstream estrogens in serum were systematically measured by using a combined sensitive UPLC-MS/MS method. The flux of different metabolic pathways of steroid hormones were analyzed. Logistic regression and ROC curve model analyses were performed to identify the potential steroid markers that were closely associated with GDM development. Results: Serum corticosteroids, progestins and almost all the estrogen metabolites via 16-pathway from parent estrogens were higher in GDM women compared with healthy controls. Most of the estrogen metabolites via 4-pathway and more than half of the metabolites via 2-pathway were not significantly different. 16α-hydroxyestrone (16OHE1), estrone-glucuronide/sulfate (E1-G/S) and the ratio of total 2-pathway estrogens to total estrogens were screened as three indicators that were closely related with the risk of GDM development. The adjusted odds ratios of GDM for the highest quartile compared with the lowest were 72.22 (95% CI 11.27-462.71, Ptrend <0.001) for 16OHE1 and 6.28(95% CI 1.74-22.71, Ptrend <0.05) for E1-G/S. The ratio of 2-pathway estrogens to total estrogens was negatively associated with the risk of GDM. Conclusions: The whole metabolic flux from cholesterol to downstream steroid hormones increased in GDM condition. The most significant changes were observed in the 16-pathway metabolism of estrogens, rather than the 2- or 4-pathway or other types of steroid hormones. 16OHE1 may be a potential strong marker associated with the risk for GDM.